Are Systemic Drug Choices for Psoriasis by Dermatologists Compatible with Psoriatic Arthritis? Data from the German National Psoriasis Registry PsoBest - Sorbe C; Kargin S; von Kiedrowski R; Thaci D; Weyergraf A; Blome C; Augustin M; Stephan B (Psoriasis: Targets and Therapy)
Christina Sorbe,1 Secilay Kargin,1 Ralph von Kiedrowski,2 Diamant Thaci,3 Ansgar Weyergraf,4 Christine Blome,1 Matthias Augustin,1 Brigitte Stephan1 1Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Hamburg, Germany; 2Medical Study & Service Selters GmbH, Selters (Westerwald), Germany; 3Institute and Comprehensive Center for Inflammation Medicine, University of Lübeck, Lübeck, Germany; 4Outpatient and Studycenter on the Hase Gbr, Bramsche, GermanyCorrespondence: Brigitte Stephan, Institute for Health Services Research in Dermatology and Nursing (IVDP), University Medical Center Hamburg-Eppendorf (UKE), Martinistraße 52, Hamburg, 20251, Germany, Tel +49 40 7410 55428, Email br.stephan@uke.deBackground: Plaque-type psoriasis (PSO) is a chronic inflammatory systemic skin disease. Psoriatic arthritis (PsA) is a frequent component requiring early treatment to prevent joint damage. Guidelines recommend differentiated drug decisions for both conditions.Objective and Methods: Descriptive analysis of drug choices for patients with PSO with or without additional PsA of the German Psoriasis registry PsoBest from 2007 to 2022.Results: The analysis comprises data of 17,310 patients with PSO: 18,6% with additional PsA (PSO+PsA), mean age 47.6 (± 14.8) years, 58.8% male, mean duration of PSO 16.4 years in patients without PsA (PSO-PsA; ± 14.3), 20.6 years in PSO+PsA (± 15.3, p < 0.001). PSO-PsA and PSO+PsA patients showed a marked burden of disease: PASI (15.7 (± 10.1) and 13.9 (± 10.6, p < 0.001)); DLQI (11.7 (± 7.2) and 12.3 (± 7.6; p < 0.001)). Before registry entry, 47.0% of patients received no systemic antipsoriatic treatment. Prior systemic medications were mainly non-biologics (40.4%), 12.6% were biologics, with a significantly higher rate in PSO+PsA patients (24.7% vs 9.8%). At registry baseline, the majority of the patients received non-biologic treatment (55.9%), with significantly higher rates for PSO-PsA patients (55.9% vs 34.8%). Biologics were used in 43.9% of all patients, with a significantly higher rate in PSO+PsA patients (65.9% vs 38.8%). Three hundred and three (9.4%) of PSO+PsA patients received treatments at baseline with approval for PSO, but not explicitly for PsA. Those patients had minor active joint involvement.Conclusion: Early and effective treatment of PsA is crucial to prevent persistent damage of the joints. Although most patients received recommended systemic treatment for PSO+PsA, there is a small number of patients with prescriptions addressing mainly the inflammation of the skin and not explicitly PsA. To choose recommended medication for both entities we need to regard the entire systemic inflammation and interdisciplinary co-working should be implemented.Keywords: biologics, systemic therapy, skin disease, dermatology